Hambatan yang Dialami Mahasiswa Praktik Pengalaman Lapangan Bimbingan dan Konseling di Sekolah dalam Pemberian Layanan Informasi untuk Menjadi Guru Profesional (Studi terhadap Mahasiwa PLBKS STKIP PGRI Sumatera Barat Periode 2012-2013) - Priono, Indra; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
Education should be basically starting from process to outcome. Education is a life activities in the community to achieve the full realization of human last a lifetime. The problem in this study is what are the barriers that prevent students practical field experience in school guidance and counseling in the provision of information services to become professional teachers. This study aimed to describe: (1) barriers experienced by students in explaining the material PPLBKS information services (2) barriers experienced PPLBKS student in classroom management while providing information services. This research is a descriptive study sought to describe a situation for what it is. The population in this study were all students practice guidance and counseling period 2012-2013, amounting to 130 students. While the sample in this study was 56 students. The instrument used in this study was a questionnaire. While the data used for the analysis of the percentage formula. Results of this study found that (1) the barriers experienced by students PPLBKS in explaining the material is in the category of information services pretty much obstacles, as many as 44 students or 78.57% of the students expressed a fair amount of resistance (2) barriers experienced by students in classroom management PPLBKS time of service quite a lot of information on the category of barriers, as many as 43 students or 76.78% of the students expressed a fair amount of resistance.Â